INOVASI MEDIA PEMBELAJARAN FLASH CARD “KEHATI” DALAM MATERI KEANEKARAGAMAN HAYATI KELAS X - Zega, Yakin Teguh; Tapilouw, Marisa Christina; Sucahyo, Sucahyo (Universitas Muhammadiyah Pontianak, 2025)
In biodiversity material, innovative contextual media with variety is needed to capture students’ attention. This research focuses on developing and evaluating the effectiveness of flash card for biodiversity topics. The study follows Research and Development methods (R&D), ADDIE Approach consisting of phase Analysis, Design, Development, Implementation, and Evaluation. The Subjects are students grade X at SMA Kristen Satya Wacana. In the analysis phase, 78% of students' difficulty with biodiversity topics, specifically in levels, distribution and the lack of existing flash card media. Based on this analysis, flash card and aquascape media have the potential for development. In the design phase, flash card media, aquascape, LKPD (Lembar Kerja Peserta Didik) and test questions were created. In the development phase, flash card media achieved was very valid (91%) and the aquascape media was very valid (87%). Trial results demonstrated that both media were very effective (81%). These results can be implemented. In the implementation phase, it showed a moderate N-gain score of 0.57. In the evaluation phase, the students’ responses were effective (75%) and the teacher responses were very effective (95%) for biodiversity topics. In conclusion, the flash card and aquascape media are very valid and effective educational tools in learning.